Optimization of Human Mesenchymal Stem Cells for Rheumatoid Arthritis: Implications for Improved Therapeutic Outcomes. Issue 2 (18th November 2021) - Breitman, Maya; Bonfield, Tracey L.; Caplan, Arnold I.; Lazarus, Hillard M.; Haghiac, Maricela; LaSalvia, Susan; Reese‐Koc, Jane; Singer, Nora G.
Abstract : Objective: Seropositive rheumatoid arthritis (RA) is a chronic autoimmune disease that is rarely "cured." Human mesenchymal stem cells (hMSCs) are known to reduce inflammation and restore immune homeostasis. However, methods for predicting therapeutic hMSC potency have not been established. The goal of these studies was to use and refine an ex vivo functional assay that determines potency of hMSCs and can then be validated in clinical trials as a potency measure of hMSCs used therapeutically to treat RA. Methods: Allogeneic hMSCs were cytokine‐stimulated, and a conditioned medium (CM) was harvested. The CM was tested for the potential to attenuate RA CD4+ T cell proliferation using suppression assays. Indoleamine 2, 3‐dioxygenase (IDO) mRNA, and protein were quantified in hMSCs as a measure to compare hMSCs across (prior) studies. Results: To mimic a proinflammatory environment that resembles that in RA, interleukin‐1(IL1β), tumor necrosis factor α (TNFα), and interferon γ (IFNγ) (alone or in combination) were used to precondition hMSCs. Treating hMSCs with a combination of these cytokines generated a CM "secretome" that suppressed T cell proliferation between 70 and 83%. Forty‐eight hours of cytokine preconditioning hMSCs was required to maximize this effect. T cell suppression positively correlated with increases in hMSC cellular IDO mRNA and protein. Conclusion: By standardizing assays to measure hMSC effects, their potency on T cell suppression can be quantified. These studies demonstrate that hMSCs can be compared functionally to identify optimal preparation(s) for therapeutic use in RA and that the potency of hMSC‐dependent T cell suppression may differ between hMSC donors. Clinical studies are warranted to validate the hypothesis that ex vivo potency in suppressing T cells will positively correlate with a reduction in RA disease activity and increase in immunological quiescence.